2013
DOI: 10.1016/j.buildenv.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol deposition in single and two-bed hospital rooms: A numerical and experimental study

Abstract: Abstract:Aerial dispersion of pathogenic microorganisms and subsequent contamination of surfaces is well recognised as a potential transmission route for hospital acquired infection. Simulation approaches such as computational fluid dynamics (CFD) are increasingly used to model Results for all layouts demonstrate that small particle bioaerosols are deposited throughout a room with no clear correlation between relative surface concentration and distance from the source. However, a physical partition separating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 42 publications
10
98
0
Order By: Relevance
“…The partitions were very effective at containing the source which has the potential to protect patients either side of the partition walls. This concurs with early studies in real hospital environments [45,46], laboratory studies with biological aerosols [38] and recent numerical modelling work [20,47].…”
Section: Ward Layoutsupporting
confidence: 69%
See 2 more Smart Citations
“…The partitions were very effective at containing the source which has the potential to protect patients either side of the partition walls. This concurs with early studies in real hospital environments [45,46], laboratory studies with biological aerosols [38] and recent numerical modelling work [20,47].…”
Section: Ward Layoutsupporting
confidence: 69%
“…This aspect must be considered in context in future design. Where the airborne transmission risk is very small, the increase due to partitions will remain small, and the advantages in terms of patient privacy and potential for reducing environmental contamination [38] will likely outweigh disadvantages. However in environments where there is a substantial airborne risk, considering the ventilation flow in conjunction with the partition will be essential.…”
Section: Ward Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated room is based on a real 32 m 3 bioaerosol chamber (King et al, 2013) and the geometry of the room is shown in Figure 4. Warm air is assumed to be supplied to the room through a high level wall mounted inlet on one side, at a constant speed of u 0 = 0.48 meters/seconds normal to the inlet (equivalent to 6 air changes per hour (ACH)) and temperature of T in = 22°C.…”
Section: Empty Room Modelmentioning
confidence: 99%
“…Turbulence was simulated using the Reynolds Stress Model (RSM) which accounts for anisotropic turbulent structures in contrast to simpler Reynolds Averaged Navier-Stokes (RANS)-based models [30]. Previous studies have shown that the RSM model yields similar flow structures to the RANS k-e model for UV simulation [25] and better prediction of bioaerosol dispersion [31] in a mechanically ventilated room. Standard wall functions were employed giving solutions with average and maximum wall y + values of 15 and 38 respectively, for the 6ACH case.…”
Section: Airflow Simulationmentioning
confidence: 99%